Shedding Light on WTO Jurisdiction and Preventing Abuse of The Security Exception Provision (Lex Scientia Law Review, 2024)
This paper critically analyzes the World Trade Organization (WTO) jurisdiction over disputes involving the use of the Security Exception (SE) under Article XXI(b) of the General Agreement on Tariffs and Trade (GATT) 1994, and explores measures the WTO could take to prevent the abuse of this provision. The study utilizes legislative, case-based, and historical approaches within a normative juridical framework to examine the complexities surrounding the invocation of the SE. First, the paper demonstrates that the WTO does indeed have jurisdiction over disputes involving the SE, countering the perception that the 'self-judging' nature of Article XXI(b) absolves the WTO of oversight. This argument is supported by the WTO panel’s ruling in Russia – Traffic in Transit and reinforced by historical precedents, which confirm that affected countries can engage in consultations with the invoking state. Second, the paper identifies two critical instruments that could prevent the abuse of the SE provision. These instruments are rooted in the interpretation of the SE’s text, guided by the ordinary meaning of its terms, in accordance with the principle of good faith. The paper argues that more precise definitions of what constitutes an emergency situation affecting state security are essential to prevent the misuse of the SE for protectionist or politically motivated purposes. Ultimately, the research calls for a more robust framework to ensure that the Security Exception serves its intended purpose—protecting legitimate national security interests—while preventing its exploitation for unjustifiable trade barriers. The WTO must develop clearer guidelines and stronger mechanisms for transparency and accountability to maintain the integrity of the global trading system.